Механизмы сезонной цикличности размножения птиц. Сообщение IV. Внешние факторы цикличности размножения - Новиков, Б.Г. (Вестник зоологии, 1975)
Data from literature and results of studies in the role of external factors for determination of birds reproduction periodicity are generalized. It is shown that the character of birds' reproduction dependence on environmental conditions is connected with their biological peculiarities and photoperiodism is a leading external factor in regulation of their reproduction.